2, 2′‐Dihydroxybenzophenones and Derivatives. Efficient Synthesis and Structure Endoscopy by DFT and NMR. Credentials as Potent Antiinflammatory Agents. Issue 10 (12th July 2016) - Tzeli, Demeter; Kozielewicz, Pawel; Zervou, Maria; Potamitis, Constantinos; Kokkotou, Katerina; Rak, Benedikt; Petrou, Anthi; Tsolaki, Evaggelia; Gavalas, Antonios; Geronikaki, Athina; Petsalakis, Ioannis D.; Tsoungas, Petros G.
Abstract: 2, 2'‐dihydroxybenzophenones and derivatives have been synthesized directly or by oxidation of their incipiently obtained benzylic alcohols by diverse efficient methods. Oxime and N‐acyl hydrazone derivatives have also been prepared. Their structure profile has been scrutinized by DFT/B3LYP‐6‐311++G** methodology, NMR spectroscopy and dihedral angle grid scan analysis. Energetically favorable conformations pointed to (i) an almost coplanar bifurcated 6‐membered H bridge in ketones, (ii) a single 6‐membered H bridge, accompanied by a 7‐membered H bonding interaction in oximes and (iii) a single 6‐membered H‐bridge in hydrazones. In the latter case, a stable conformation with an additional 9‐membered pseudo ring was also found. Highly deshielded protons in the NMR spectra are in accordance with the theoretically obtained findings on the H‐bonded conformers. Significant anti‐inflammatory activity of the compounds has been found by in vivo tests with their oxime and hydrazone derivatives showing the highest activity, hydrazone11, in partucular, competing with marketed drugs. In silico docking studies point to the perspective potency of these structures as COX‐1/COX‐2 inhibitors. Abstract : Ligand‐based designed target structures have been prepared by diverse and efficient approaches. Highly deshielded intramolecularly H‐bonded protons in their NMR spectra are in accordance with DFT findings. Experimentally demonstrated significant anti‐inflammatory activity singled out oxime and hydrazone derivatives as most potent ones.